Postexercise left ventricular function and cTnT in recreational marathon runners - George, K.; Whyte, G.; Stephenson, C.; Shave, R.; Dawson, E.; Edwards, B.; Gaze, D.; Collinson, P. (Medicine & Science in Sports & Exercise, 2004)
Purpose: To assess the impact of prolonged exercise on left ventricular (LV) function and the appearance of cardiac troponin T (cTnT) in older and recreational athletes. Methods: Heart rate (HR), blood pressures, and cTnT were recorded in 35 subjects (age range 22-57 yr, finishing time 157-341 min) pre- and postrace. Echocardiograms (N = 26) assessed stroke volume (SV), ejection fraction (EF), sBP/LV end-systolic volume (sBP/ESV), diastolic filling (E:A ratio) as well as preload (LV internal dimension at end-diastole [LVIDd]) and afterload (LV wall stress). HR and core temperature were recorded in-event. Prepost changes in LV function were analyzed by repeated measures t-test. Delta scores for LV function and cTnT data were correlated with each other, age, finishing time, alterations in loading, and in-event data. Results: SV was significantly decreased postrace (109 +/- 31 vs 85 +/- 25 mL, P < 0.05) likely due to a significant decrease in LVIDd (5.3 +/- 0.4 vs 4.9 +/- 0.5 cm, P < 0.05; r = 0.80, P < 0.05). LV wall stress was unchanged postrace (90 +/- 25 vs 89 +/- 27 g[middle dot]cm-2, P > 0.05). EF (70 +/- 12 vs.70 +/- 10%, P > 0.05) and sBP/ESV (3.7 +/- 2.9 vs 4.0 +/- 2.0, P > 0.05) did not change prepost race and were not related to age or finishing time (P > 0.05). E:A ratio was significantly reduced postrace (1.73 +/- 0.38 vs 1.41 +/- 0.25, P < 0.05) and could not be explained by an increased HR (56 +/- 9 vs 84 +/- 10, P < 0.05; r = 0.08, P > 0.05), a reduced LVIDd (r = 0.11, P > 0.05), age, finishing time, or in-event data. Postrace 26/33 subjects presented cTnT values in the range 0.024-0.080 [mu]g[middle dot]L-1 that were not related to changes in LV function, loading, age, finishing time, or in-event data. Conclusion: No evidence of load-independent depression in LV systolic function was reported. Changes in cTnT and E:A were not related, and their etiology is uncertain.